دور تكنولوجيا الاعلام والاتصال في تقييم أداء الموارد البشرية – دراسة ميدادنية لعدد من المؤسسات الاقتصادية - مزياني أمين (جامعة الوادي University Of Eloued, 2024)
هدف هذه الدراسة هو فهم تأثير وتكنولوجيا الاعلام والاتصال على أداء الموارد البشرية، وكيف يمكن لهاذين المفهومين التكامل فيما بينهما لتحقيق أهداف المؤسسة، كما يتناول الهدف الرئيسي للدراسة مجموعة من المحاور، منها: تحليل التأثيرات التكنولوجية على إدارة الموارد البشرية، فهم كيف يؤثر التقدم التكنولوجي على إدارة الموارد البشرية وكيف يمكن استثمار هذه التأثيرات لتحسين عمليات إدارة الموارد البشرية، دراسة تأثير إدارة الموارد البشرية على تكنولوجيا الاعلام والاتصال، تحديد التوجيهات لتحسين ممارسات إدارة الموارد البشرية واستخدام التكنولوجيا و توفير توجيهات وتوصيات عملية للمؤسسات لتحسين إدارة الموارد البشرية وتكنولوجيا الاعلام والاتصال بشكل فعّال، ومن خلال استكشاف هذه الجوانب، سعت الدراسة إلى توفير رؤى شاملة وتوجيهات قيمة تدعم التحول والتطوير في بيئات العمل الحديثة. The aim of this study is to understand the impact of information and communication technology on human resource performance and how these concepts can integrate to achieve organizational goals. The main objective of the study covers various aspects, including analyzing technological impacts on human resource management, exploring how technological advancements affect HR management, leveraging these impacts to enhance HR processes, studying the influence of HR management on information and communication technology, identifying guidelines to improve HR management practices and technology use, and providing practical recommendations for organizations to effectively enhance human resource management and information and communication technology. Through exploring these facets, the study seeks to offer comprehensive insights and valuable guidance supporting transformation and development in modern work environments.
The role of information and communication technology in assessing human resources performance A field study of severaleconomicinstitutions
Keywords: الموارد البشرية; الأداء; الأداء الشامل; تكنولوجيا الاعلام والاتصال; تقييم الأداء; Human resources; performance; comprehensive performance; information and communication technology; performance evaluation